Modulatory Effect of Medicinal Plants and Their Active Constituents on ATP-Sensitive Potassium Channels (KATP) in Diabetes - Lina T. Al Kury (MDPI AG, 2023)
Hyperglycemia, which is a chronic metabolic condition caused by either a defect in insulin secretion or insulin resistance, is a hallmark of diabetes mellitus (DM). Sustained hyperglycemia leads to the onset and development of many health complications. Despite the number of available antidiabetic medications on the market, there is still a need for novel treatment agents with increased efficacy and fewer adverse effects. Many medicinal plants offer a rich supply of bioactive compounds that have remarkable pharmacological effects with less toxicity and side effects. According to published evidence, natural antidiabetic substances influence pancreatic β-cell development and proliferation, inhibit pancreatic β-cell death, and directly increase insulin output. Pancreatic ATP-sensitive potassium channels play an essential role in coupling glucose metabolism to the secretion of insulin. Although much of the literature is available on the antidiabetic effects of medicinal plants, very limited studies discuss their direct action on pancreatic KATP. The aim of this review is to focus on the modulatory effects of antidiabetic medicinal plants and their active constituents on pancreatic KATP. The KATP channel should be regarded as a key therapeutic milestone in the treatment of diabetes. Therefore, continuous research into the interaction of medicinal plants with the KATP channel is crucial.